Ideal Baby Height And Weight Monitoring Design - Setiawan, Bagus; Ariyadi, Tamsir; Fitriani, Endah; Paramitha, Nina (Program Studi Teknik Elektro Universitas Khairun, 2025)
Growth and development of infants are crucial aspects that need to be regularly monitored, with height and weight serving as key indicators of nutritional status. This study aims to design and develop a technology-based system to automatically monitor the height and weight of infants using ultrasonic sensors and load cells. The system is designed to provide accurate, practical, and continuous real-time measurements, integrating technologies such as ESP32, LCD, and Blynk application. Test results demonstrate that the system achieves high accuracy with an error percentage below 1%, along with optimal performance of the ultrasonic sensor (distance up to 80 cm) and load cell (weight up to 10 kg). Among the 6 samples tested, 2 infants were categorized as undernourished, 4 as normal. This system is expected to simplify the monitoring of infant nutritional status, support early detection of health issues, and contribute to improved growth quality